Multipurpose utensil - Irwan, Ammar Zareeq; Abdullah, Muhammad Ilhamie; Mohd Hilmi, Muhammad Aizzad; Mazalan, Muhammad Hanif; Hassnol Zulkarnaen, Hadzwan Syahmi; Kamaron, Muhammad Hanif; Azis, Siti Noraziana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
People with disabilities first investigate a variety of facets of their life, such as work, education, social inclusion, and technology. But they frequently run into problems and find it tough to deal with some things in their day-to-day life. Future. Co. is committed to meeting the needs of disabled people with this. It will go over the goods and services offered by the business to improve the lives of those with disabilities, such job training programs, accessible solutions, and assistive technology. The company's goals, principles, and influence on the blind community could also be included, as well as its initiatives to support inclusion, equality, and the empowerment of people with disabilities.